The more ambidexterity the better? The moderating effect of organizational learning between high-performance HR practices and organizational performance - Wang, Canhao; Zhang, Meng; Ma, Hongtao (Frontiers in Psychology, 2024)
The objective of this study is to test the directly impact of high-performance HR practices on organizational performance, and the mediating effect of organizational ambidexterity empirically. Moreover, the moderating role of organizational learning in the relationship between ambidexterity and specialization in exploitation or exploration on firm performance has also been examined. Untimately, we construct a moderated mediation model.Questionnaires were distributed to the target enterprises mainly through the contacts of the research group members, the local management consulting association and the training opportunities for leaders. Finally, a total of 347 CEO questionnaire data were collected from Chinese SMEs. The sample cover Shanghai,